ANALISIS KEBIJAKAN AGRARIA PASCA-REFORMASI (Solusi, 2022)
More than 20 years of reform in Indonesia, however, specifically in the issue of agrarian reform, many civic groups and academics consider that the agenda has not become a serious concern for every post-Reform Indonesian President. People still often have to deal with Corporations in order to defend their own land, which has been occupied and cultivated for so long. The high level of agrarian conflicts shows that this commitment is not serious. Especially with the birth of the Job Creation Act which is considered to be a big obstacle for the people. This paper aims to analyze the post-reform agrarian policy, and uses the perspective of the Fifth Precepts of Pancasila and Article 33 of the 1945 Constitution as the philosophical, ideological, and juridical foundations. And using normative research. Researchers try to elaborate on how the ideal conception of agrarian reform in Indonesia and also the realization of policies from this ideal conception by Indonesian leaders post-reform.